MEASUREMENT OF PATIENT SATISFACTION BASED ON THE QUALITY OF INTERACTION WITH NURSES IN PUBLIC HOSPITALS IN INDONESIA - Nabila, Rahma; Raharjo, Slamet; Rahayu Pramadya, Sugeng (Jurnal Multidisipliner Bharasa, 2024)
This study aims to measure patient satisfaction based on the quality of interaction with nurses in public hospitals in Indonesia. The quality of interaction between nurses and patients is one of the important indicators in determining the level of patient satisfaction with health services. This study uses a quantitative method with a survey approach, where data is collected through questionnaires distributed to patients in several public hospitals. The variables analyzed included communication, empathy, attention, and responsiveness of nurses in serving patients. The results showed that there was a significant positive correlation between the quality of nurse-patient interaction and the level of patient satisfaction. Effective communication and empathetic attitudes of nurses have proven to be the main factors that affect patients' perception of the quality of services received. In addition, the attention and responsiveness of nurses in handling patient complaints also contributes significantly to the level of satisfaction. The implications of this study show that improving the quality of interaction between nurses and patients can be an effective strategy in increasing patient satisfaction in public hospitals. Therefore, training that focuses on improving nurses' communication and empathy skills is highly recommended to be implemented in hospitals. Thus, better health services can be achieved, which ultimately contributes to improving the quality of life of patients in Indonesia.